Hadis-Hadis tentang Amalan Untuk Orang yang Telah Wafat (Analisis Pemahaman Ulama Perti pada Majalah Soearti) - Edriagus Saputra; Kia Mudin; Azamel Fata (Hikmah, 2022)
This study aims to analyze the understanding of the hadith of the Perti scholars contained in Soearti magazine which discusses the deeds intended for the deceased, to eliminate differences among the community and can produce a complete understanding of the scholars related to the hadith. This study uses a qualitative method with a library research model (library review). Data sources consist of primary data sources, namely Soearti magazine and the main book of hadith, and secondary data sources, namely the results of relevant research from books or journals. The results of this study are about understanding the traditions of the practices carried out for people who have died, namely: first, the validity of the hadiths contained in the Soearti magazine which explains the practices aimed at people who have died are valid (Maqbul) and narrated by Imam Bukhari and Muslims. While the understanding of the hadith about the practice given to people who have died is allowed and Soearti magazine states, that the practice reaches the person who dies, so that it can provide convenience and benefits for the person who died, such as praying and reading the Qur'an. and alms and other deeds.